Blood Cytokine, Chemokine and Gene Expression in Cholestasis Patients with Intractable Pruritus Treated with a Molecular Adsorbent Recirculating System: A Case Series. (2012) - Lisboa, Luiz F; Asthana, Sonal; Kremer, Andreas E; Swain, Mark; Bagshaw, Sean M; Gibney, Noel; Karvellas, Constantine J
Abstract : BACKGROUND: The molecular adsorbent recirculating system (MARS) is an albumin-dialysis modality that has been investigated predominantly in patients with acute and acute-on-chronic liver failure. OBJECTIVES: To report the clinical efficacy and safety of MARS therapy for intractable pruritus in cholestasis patients with stable chronic liver disease, characterizing the impact of MARS on cytokine levels and on the transcriptome in the blood compartment. METHODS: MARS therapy was performed on three patients with cholestatic liver disease using 8 h runs for two consecutive days. The expression levels of 65 cytokines/chemokines and 24, 000 genes were profiled by Luminex (Luminex Corporation, USA) and microarray, respectively. RESULTS: A quality-of-life assessment demonstrated a marked improvement during therapy, which was sustained in two of three patients. No bleeding or infectious complications were observed. Bile acid levels were markedly reduced following MARS (mean [± SD] pretreatment 478.9±112.2 μmol/L versus post-treatment 89.7±68.8 μmol/L). Concordant decreases in cytokine/chemokine levels were noted for interleukin (IL)-1beta, IL-2, IL-6, IL-8, IL-12 (p40), RANTES, tranforming growth factor-alpha, tumour necrosis factor-alpha and thrombopoietin following MARS. On microarray profiling, biologically relevant concordant changes among all patients were evident for 20 different genes (10 upregulated and 10 downregulated). The upregulation of several potentially immune suppressive/regulatory genes (eg, early growth response 3 [ EGR-3 ], ephrin-A2 [ EFNA2 ] and serum amyloid A1 [ SAA1 ]), concurrent with downregulation of genes involved in innate immunity (eg, toll-like receptor 4 interactor with leucine-rich repeats [ TRIL ]) and inflammation (eg, ephrin receptor B1 [ EPHB1 ]), was observed. CONCLUSIONS: This investigative approach offers new insights into intractable pruritus and suggests future therapeutic targets. The clinical benefit of MARS in cholestasis patients with intractable pruritus may not exclusively result from filtration of pruritogens, but also from systemic changes in cytokine/chemokine levels and changes in gene expression of blood cells.